Representasi Mental Kosakata Konkret dan Abstrak dalam Working Memory Mahasiswa: Kajian Psikolinguistik: Mental Representation of Concrete and Abstract Vocabulary in Students’ Working Memory: A Psycholinguistic Study - Mustakim Saleh; Isna Dia'ul Adha; Elya Febriani (Universitas Tidar, 2026)
This study aims to analyze the differences in memory recall between concrete and abstract vocabulary from the perspective of Working memory among university students. The study employed a quantitative approach using a simple experimental (within-subject) design. The participants consisted of 112 university students. The research instrument included two vocabulary lists containing 20 concrete words and 20 abstract words. Participants were asked to observe the word lists for 60 seconds and subsequently recall the words within 2–3 minutes. The data were analyzed using descriptive statistics and a paired sample t-test. The findings revealed that the mean score for concrete vocabulary recall was 11.688, whereas the mean score for abstract vocabulary recall was 9.491. The paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between concrete and abstract vocabulary recall. These findings suggest that concrete words are easier to remember because they possess stronger visual and verbal representations within the cognitive system. This study reinforces Dual coding theory in the context of language processing among university students and provides practical implications for vocabulary learning strategies based on visualization.